Emotional Eating and Spicy Food Consumption Related to Dyspepsia in Female Adolescents: A Literature Review - Salma Violita Pradana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Dyspepsia is a highly prevalent functional gastrointestinal disorder, particularly among adolescents, and Indonesia has one of the highest reported prevalence rates globally. Recent literature has highlighted the potential role of behavioral and dietary factors, such as emotional eating and spicy food consumption, in the development and exacerbation of dyspeptic symptoms. This review focuses on female adolescents, a population shown to be more vulnerable to emotional and hormonal fluctuations that may increase susceptibility to digestive disturbance. Peer-reviewed articles from the last decade were identified through Pubmed and Google Scholar, then selected based on relevance to the themes of emotional eating, spicy food intake, and dyspepsia. Thematic analysis of the included studies reveals consistent evidence of a link between emotional eating and high energy-dense and irritant food intake, including spicy foods, while frequent consumption of spicy food itself was significantly associated with dyspeptic symptoms such as epigastric pain, bloating, and early satiety. Furthermore, the co-occurrence of emotional and dietary stressors had synergistic effects on the risk of dyspepsia in female adolescents. Further robust, longitudinal, and controlled studies are needed to clarify the mechanism involved. Nevertheless, current evidence supports the inclusion of behavioral and dietary assessment in the early identification and management of dyspepsia in adolescent females.